The Influence of Financial Performance against Stock Prices in Companies Listed in LQ45 Index 2012 - 2016 Period - Henry Wijaya, John; ., Gusni; ., Kartika (International Journal of Engineering and Technology, 2018)
This study aims to determine the effect of financial performance of each variable on stock price of the companies listed in the LQ45 Index in 2012 â€“ 2016. This type of research used in this research is explanatory research with descriptive research method and correlation. This study used secondary data. The research population comprised LQ45 companies in 2012-2016 consisting of 45 companies. The sample was selected by the purposive sampling technique and 21 companies were included in the research sample. The data analysis technique was panel data regression using the random effect model. The results of the study showed that earnings per share had a significant effect on stock price. Cash position had a significant effect on stock price. Trading volume had a significant effect on stock price. While return on equity, debt to asset ratio and firm size did not have significant effect on stock price. The results of research F-test showed that the model in regression equation is just right. The coefficient of determination (R2) in this study was 0.758096. This means that the contribution of all independent variables was explained the dependent variable was 75.8%, while the remaining 24.2% was explained by independent variables outside the model.Â Â